2014
DOI: 10.17269/cjph.105.4150
|View full text |Cite
|
Sign up to set email alerts
|

Associations between family eating behaviours and body composition measures in peri-adolescents: Results from a community-based study of school-aged children

Abstract: OBJECTIVES:To identify key eating behaviours in children and their parents and to determine the associations between these behaviours and measures of body composition in children. METHODS:Data were collected on a sample of 431 peri-adolescent children (12.4±0.3 years) and their parents from the Niagara Region. Body composition was assessed by trained research assistants. Eating behaviours were assessed using a revised version of the Family Eating and Activity Habits Questionnaire. Principal component analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…It is also in line with previous experimental research, indicating that distraction may trigger overeating in dieters (Hetherington et al, 2006;Ward and Mann, 2000). Furthermore, it reflects concerns over 'eating on the go' and the potential impact on overeating and weight gain (Hajna et al, 2014;Ogden, 2014). Therefore, the results indicate that eating while walking may disinhibit those higher in restrained eating triggering overeating at a subsequent meal.…”
Section: Discussionsupporting
confidence: 88%
“…It is also in line with previous experimental research, indicating that distraction may trigger overeating in dieters (Hetherington et al, 2006;Ward and Mann, 2000). Furthermore, it reflects concerns over 'eating on the go' and the potential impact on overeating and weight gain (Hajna et al, 2014;Ogden, 2014). Therefore, the results indicate that eating while walking may disinhibit those higher in restrained eating triggering overeating at a subsequent meal.…”
Section: Discussionsupporting
confidence: 88%
“…There was large variation among studies for the number of participants (112–15,973) and age of children (3.6–18 years). Twelve articles reported the association between eating meals while TVV with overweight or obesity , and four articles used abdominal obesity or waist circumferences as the primary outcome measure . Nine articles examined the relationship between eating any meal (did not specified the meal) while TVV, while nine articles specified breakfast, lunch or dinner (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…interventional studies) (n = 6). Twenty relevant articles (4,5,(10)(11)(12)(13)(14)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)31) were identified for the systematic review, of which eight articles (5,10,12,13,20,25,26,31) reported OR for overweight/ obesity and were therefore included in the meta-analysis. Only one of the eight articles (5) assessed obesity as an outcome; we therefore included overweight in the meta-analysis.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…It may be that parents of overweight/obese children use food to help their children feel better or overcome emotions. A previous study also reported that emotional eating behaviors such as "eating when bored" or "eating when upset/ anger" were positively associated with children's BMI values [16]. However, compared to other family food choice motives, items in the "mood" subscale scored the lowest ("cheers up our family"=5.08; "helps us relax"=4.20 and "keeps us awake"=3.84) among all participants including parents of overweight/obese children.…”
Section: Discussionmentioning
confidence: 88%